Effect of Short Term Cardiac Rehabilitation Program on Quality of Life in Patients with Coronary Artery Disease - Ina Marita; Sunaryo B. Sastradimaja; Badai Bhatara Tiksnadi (Althea Medical Journal, 2017)
Background: Cardiac rehabilitation (CR) programs are known to be one of the effective managements which aim to improve the quality of life (QoL) in coronary artery disease (CAD). However, there is still controversy about the effect on QoL dimension. The purpose of this study is to determine the effect of short term cardiac rehabilitation program on quality of life in patients with coronary artery disease.Methods: The study design used was a quasi experimental study with repeated measurements in consecutive sampling involving 11 subjects with CAD from September–November 2015 in Cardiorespiratory Clinic and Gymnasium of Physical Medicine and Rehabilitation and Cardiac Unit Services, Dr. Hasan Sadikin General Hospital Bandung. The cardiac rehabilitation program was performed for 4 weeks. The quality of life was scored using medical outcomes study short form 36 (SF-36) questionnaire before and after CR program. Statistics obtained in this study were analyzed using paired t-test and Wilcoxon test.Results: This study involved 11 male patients with CAD with an average age of 58 (11) years old with the diagnosis of CAD post CABG (n=6), CAD post PCI (n=4), and CAD unrevascularized (n=1). The average total score of quality of life questionnaire SF-36 demonstrated a significant increase (p<0.001) after CR program 87.27(8.5) as compared to before CR program 49.09(8.4). This improvement occurred in all QoL dimensions.Conclusions: Short term cardiac rehabilitation program can improve the quality of life in patients with coronary artery disease.